(untitled) (Journal of actual problems of jurisprudence, 2026)
In the independent Republic of Kazakhstan, higher legal education is currently in a developmental stage and requires significant quality enhancement. This scientific article proposes the introduction of artificial intelligence (AI) technologies, leveraging both national and international legal norms to expedite this implementation. The challenge of integrating AI into the educational process is not merely a domestic issue but one of global significance. Law faculties worldwide, irrespective of their prominence, should incorporate AI technologies into the teaching of all legal disciplines, given AI’s almost limitless potential. The authors of this article, focusing on the law faculties of universities in the Republic of Kazakhstan and their academic subjects, seek to present their scholarly perspective on the specific application of various AI tools in teaching several legal disciplines. Through their analysis, the authors recommend the development and enactment of new Kazakh laws, by-laws, and international conventions to incorporate AI mechanisms in all sectors of society, including higher education, to improve the quality of higher legal education in the country. The proposed international conventions advocate for the use of AI for the benefit of the global community and individual states while also establishing norms to mitigate risks and develop methods to thwart hostile hacker actions that could compromise international security. This topic is being examined for the first time within Kazakh science, and its approaches may interest law faculties in other countries. Keywords: artificial intelligence, Kazakh legal norms, international legal norms, quality of education, implementation of AI, neural networks, convention, law.